Neuroprotective effects of traditional Chinese medicine formulas in animal models of retinal degenerative diseases: a systematic review and meta-analysis - Xu, Yunxi; Mi, Qindong; Yong, Qi; Xu, Chao; Zhao, Dingmeng; Wang, Chuning; Jiang, Zhongshan; Yu, Chenghao; Ye, Hejiang (Frontiers in Pharmacology, 2026)
PurposeRetinal degenerative diseases (RDDs) cause irreversible vision loss with limited treatment options. Traditional Chinese medicine (TCM) formulas have demonstrated neuroprotective effects, yet their overall efficacy lacks comprehensive meta-evidence. The aim of this study was to exploratively evaluate the neuroprotective effects of TCM formulas in animal RDD models.MethodsA comprehensive literature search was conducted across eight electronic databases to identify animal studies that evaluated the neuroprotective effects of TCM formulas on RDDs. Pairwise meta-analysis and Bayesian network meta-analysis (NMA) were performed to synthesize evidence on key outcomes: neural growth, glial activation, oxidative stress, apoptosis factors, and ophthalmological parameters. Treatment rankings were assessed using the surface under the cumulative ranking curve (SUCRA).ResultsTwenty-four studies were included. The compositions and bioactive compounds of the TCM formulas have been defined and identified. Pairwise meta-analysis demonstrated that specific TCM formulas might exert neuroprotective effects on RDDs by regulating key biomarkers. Specifically, Zhen-Bao-Wan, Bu-Shen-Yi-Jing-Fang, and Qi-Shen-Yi-Qi pills modulated neural growth and glial activation by upregulating BDNF, CNTF, and reducing GFAP, respectively. Furthermore, Yi-Qi-Wen-Yang-Tong-Luo decoction, Zi-Yin-Ming-Mu decoction, and Yishi-Tablet suppressed oxidative stress and apoptosis by reducing SOD, retinal apoptotic cells and caspase-3, respectively. Additionally, Bu-Yang-Huan-Wu decoction improved retinal function by elevating ERG-a and ERG-b wave amplitudes. Subgroup analyses indicated that Bu-Yang-Huan-Wu decoction and Qu-Yu-Tong-Luo prescription exhibited superior efficacy in restoring retinal ganglion cell (RGC) counts and retinal thickness in specific RDD models. The NMA results indicated that the included TCM formulas exhibited target-specific and dose‒response trends, with different formulas showing preferential efficacy for distinct biomarkers. Given the limitations identified in this study, these findings should be interpreted as preliminary evidence to guide future research rather than as conclusive results. Future studies with rigorous experimental designs are needed to address these limitations and enhance translational relevance.ConclusionThis study provides preclinical and exploratory evidence that the included TCM formulas might exert neuroprotective effects on animal models of RDDs by modulating glial activation, promoting neuronal growth, and inhibiting oxidative stress and apoptosis. Additional high-quality preclinical studies are essential to validate these effects and inform future clinical translation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251002491 identifier CRD420251002491.